Pemikiran Ahmad Muhamad Mustain Nasoha tentang Nasionalisme Islami sebagai Basis Cinta Tanah Air - Aqila Hasna Nabihah; Anggita Kharisma Maharani; Muhammad Fahmi Syihab; Zaskia Novita Nadila Fahima (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article examines Ahmad Muhamad Mustain Nasoha’s thought on Islamic nationalism as the basis of patriotism. Nasoha emphasizes that nationalism does not contradict Islamic teachings; in fact, the values of faith, morality, and brotherhood in Islam can strengthen national consciousness. According to him, love for the homeland is not merely a slogan or rhetoric, but a manifestation of faith and a Muslim’s social responsibility that requires active involvement in preserving unity, upholding justice, and contributing to national development. This article highlights the historical, philosophical, sociological, political, educational, and theological aspects of Islamic nationalism, including the contributions of Islamic scholars and organizations in shaping national identity as well as in the formulation of Pancasila as the state’s foundation in harmony with Islamic values. Furthermore, the article discusses the relevance of Islamic nationalism in addressing contemporary challenges, such as Indonesia’s plural society, globalization, radicalism, and digital disinformation. Nasoha stresses the importance of harmonizing Islamic values with Pancasila, so that Islamic nationalism can serve as both social cohesion and an ethical guideline for citizens. The implementation of Islamic nationalism can be carried out through education, legal reinforcement, moral development, and concrete social contributions, enabling Muslims to preserve their religious identity while actively participating in national life. Through this comprehensive study, the article asserts that Ahmad Muhamad Mustain Nasoha’s ideas significantly contribute to the development of a moderate, inclusive nationalism grounded in Islamic values. His thought offers a strategic framework to cultivate patriotic young Muslims without compromising religious identity. while strengthening Indonesia’s national integrity in the face of contemporary challenges.